Evapotranspiration and energy balance measurements over a soybean field in the semiarid sowthwestern region of Buenos Aires province (Argentina) - Cargnel, M. D. (2017)
Fil: Cargnel, M. D. Universidad de Buenos Aires. Facultad de Agronomía. Buenos Aires, Argentina.